PENGARUH IKLAN TELEVISI DAN ONLINE CUSTOMER REVIEW TERHADAP KEPUTUSAN PEMBELIAN PADA MARKETPLACE SHOPEE DI BALI - Pande Ketut Ribek; Ni Putu Nita Anggraini; Ni Kadek Ratna Kumalasari (Universitas Mahendradatta, 2022)
Growing using marketplace where as online shopping is driven by thetechnological advances that it becomes a trend to the society. Through increase of sales,required of many companies to participate using the digitization currently. A unique andgood television commercials will be easier in the mind of consumers the brand. Theexistence feature of online customer review can decrease received risk of possibility toconsumers online shopping, therefore companies and merchants that can get of the trustwhile consumer of making purchase decisions.The research population is all the Shopeeusers in Bali with was 100 respondents of sample based on purposive samplingtechnique. The data was collected by distributing questionnaire by multiple linearregression analysis.The results of analysis regression show that television advertising and onlinecustomer review the partial has positive and significant effect on purchase decisions.Based on this result, we can suggested that Shopee must to increase of the frequencybroadcasting television advertising and continue to improve advertising innovate andonline review features to create more purchase decisions.